Does Voice Therapy Improve Vocal Outcomes in Vocal Fold Atrophy?. (June 2021) - Bick, Emma; Dumberger, Lukas D.; Farquhar, Douglas R.; Davis, Heather; Ramsey, Elizabeth; Buckmire, Robert A.; Shah, Rupali N.
Objectives: Vocal fold atrophy is increasingly identified in the geriatric population. Current literature shows varying outcomes with voice therapy. Our goal was to analyze multidimensional vocal outcomes of these patients who underwent voice therapy. Secondary aims included determining compliance and analyzing differences in patients who undergo surgery. Methods: 197 patients with vocal fold atrophy were included and reviewed. Patients were categorized by treatment received. Patient-reported, perceptual, aerodynamic, and acoustic voice outcomes were analyzed before and after therapeutic intervention. Changes were calculated and significance determined using Wilcoxon signed-rank and rank-sum tests. Results: 89(45%) received no therapy, 43(22%) incomplete therapy, 51(26%) complete therapy, 8(4%) surgery only, and 6(3%) therapy followed by surgery. Those who completed voice therapy showed significant improvement in voice related quality of life (VRQOL) ( P  = .0225), glottal function index (GFI) ( P  < .001), grade, roughness, breathiness, asthenia, strain (GRBAS) ( P  < .001), maximum phonation time (MPT) ( P  = .0081), and fundamental frequency in women ( P  = .0024). No significant changes were found in mean airflow. When comparing patients who underwent surgery versus voice therapy, statistically significant differences were present between pre-treatment VRQOL ( P  = .0269) and GFI ( P  = .0166). Conclusions: Only 29% of patients with vocal atrophy completed voice therapy when recommended. Within this patient cohort, voice therapy results in significant improvement in multidimensional voice outcomes. Patients with vocal atrophy that undergo surgical treatment differ from those treated with voice therapy alone in their pre-treatment patient-reported measures.